Marketing Optimization Through Digital Advertising in “Kobamie Jaya” Cooperatives, Kendal District - Ahmad Sehabuddin; Joko Widodo; Indri Murniawaty (Universitas Negeri Semarang, 2023)
Business development is increasingly rapid and competition is getting sharper in capturing market share, companies are required to be able to empower their resources effectively and efficiently so that companies can have a competitive advantage. Kobamie Cooperative aims to prosper its members by expanding market share, especially in the use of digital media. However, in this case the Kobamie Cooperative has not been able to maximize its broad market share. In this case, the use of digital advertising has not been maximized. The solutions offered to overcome partner problems are training and assistance in strengthening marketing through digital advertising. The methods used in the community service include socialization activities, training, mentoring and evaluation of community service programs. The result of this community service is to increase partners' understanding of the concept of digital advertising, partners are able to practice, compose interesting content and images to be used as advertisements and partners are able to post advertisements via digital platforms. The conclusion of this community service is that this community service helps partners in marketing products via digital. Perkembangan bisnis yang semakin pesat dan persaingan semakin tajam dalam merebut pangsa pasar, perusahaan dituntut untuk dapat memberdayakan sumber daya yang dimiliki secara efektif dan efisien agar perusahaan bisa mempunyai keunggulan bersaing. Koperasi Kobamie bertujuan untuk mensejahterakan anggotanya dengan memperluas pangsa pasar terutama dalam penggunaan media digital. Namun, dalam hal ini Koperasi Kobamie belum bisa secara maksimal meraih pangsa pasar yang luas. Dalam hal ini disebabkan karena penggunaan digital advertising yang belum maksimal dilakukan. Solusi yang ditawarkan untuk mengatasi permasalahan mitra yakni pelatihan dan pendampingan dalam penguatan pemasaran melalui digital advertising. Metode yang dilakukan dalam pengabdian meliputi kegiatan sosialisasi, pelatihan, pendampingan dan evaluasi program pengabdian. Hasil dari pengabdian ini adalah meningkatkan pemahaman mitra tentang konsep digital advertising, mitra mampu mempraktekkan, menyusun konten dan gambar yang menarik untuk dijadikan iklan serta mitra mampu memposting iklan via platform digital. Kesimpulan dari pengabdian ini adalah dengan adanya pengabdian ini membantu mitra dalam memasarkan produk via digital.